The Effectiveness and Relevance of Social Security Allowance in Nepal - Malakar, Indra (Tribhuvan University Journal, 2018)
This study attempts to analyze the effectiveness and relevance of Social Security Allowance (SSA) among the beneficiaries of Kirtipur Municipality 7, Kathmandu district. This study is based on primary data collection in terms of use of the allowance, sufficiency or insufficiency of the distributed amount and use of it to maintain the social status. The problems associated with the respondents along with the program were also purposively selected to verify the objectives. This study reveals that social security allowance have been used for the fulfillment of recipients basic personal needs. The effectiveness of this allow ace is highly appreciable.